2019
DOI: 10.1016/j.mtla.2019.100348
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyaluronic acid on the corrosion of an orthopedic CoCrMo-alloy in simulated inflammatory conditions

Abstract: During joint inflammation, various reactive oxygen species (ROS) are present in the surrounding tissue and joint fluid. In the laboratory, hydrogen peroxide (H 2 O 2) is typically used to simulate inflammatory conditions, and media containing proteins and hyaluronic acid (HA) are employed to simulate joint synovial fluid. Electrochemical interactions between H 2 O 2 and HA in the presence of a CoCrMo surface are expected, since HA molecules contain redox-active moieties. We hypothesized that any redox reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 33 publications
5
21
0
Order By: Relevance
“…The Chi‐squared values (squared sum of weighted residuals, also called Goodness of Fit) are in the order of magnitude of 1E‐04 – 1E‐05, documenting a good fit of the model circuit (the smaller the Chi‐squared value, the better the fit). The resistance of the bulk solution ( R S ~ 54 Ω cm 2 ) corresponds to the values found, under identical conditions, in a previous study 21 . At the outer interface, capacitive values ( Q OUT ) were generally higher in the presence of HA, suggesting adsorption of HA at this interface.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The Chi‐squared values (squared sum of weighted residuals, also called Goodness of Fit) are in the order of magnitude of 1E‐04 – 1E‐05, documenting a good fit of the model circuit (the smaller the Chi‐squared value, the better the fit). The resistance of the bulk solution ( R S ~ 54 Ω cm 2 ) corresponds to the values found, under identical conditions, in a previous study 21 . At the outer interface, capacitive values ( Q OUT ) were generally higher in the presence of HA, suggesting adsorption of HA at this interface.…”
Section: Resultssupporting
confidence: 85%
“…The protein and HA concentrations used in this study relate to the synovial fluid of patients after total hip replacement 20 . Details about the electrolyte preparation have been described earlier 21 …”
Section: Methodsmentioning
confidence: 99%
“…Our group has previously reported that 1 mM H 2 O 2 in 1X PBS had a complete lethal effect on U937 cells cultured on CoCrMo discs (Shi, 2016), compared to the lowest viability achieved in this work with 1 mM H 2 O 2 in synthetic synovial fluid trials (55%). We hypothesize that H 2 O 2 had similar interactions with solution HA as previously reported (Radice et al, 2019), where HA redox‐active moieties mitigate the oxidizing effect of H 2 O 2 . GSH I / I O results suggest that the RAW 264.7 cells were effectively metabolizing ROS using GSH, with several high viability readings corresponding with larger GSH intensities.…”
Section: Discussionsupporting
confidence: 80%
“…Some of the major constituents of synovial fluid are not found in simple FBS solutions used for tribological testing yet have been proven to be significantly influential to the joint environment and implant functionality. For example, HA and metal ions directly impact inflammatory properties, surface‐solution interactions, and organometallic composite layer formation surrounding the artificial joint (Radice, Yao, Babauta, Laurent, & Wimmer, 2019). HA in addition to proteoglycans and proteins competitively adsorb to the surface of implants, contributing to a multilayer film composite on top of the metal‐oxide film and underneath a much thicker albumin‐phosphate layer (Muñoz & Mischler, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation